Resolution of Refractory Hypertension Following Radical Nephrectomy for Renal Cell Carcinoma: A Case Report from Somalia in Resource Limit Setting - Ali RM; Omar AA; Ali IA (Cancer Management and Research, 2025)
Rahmo Mohamed Ali,1 Abdullahi Abdirahman Omar,1 Ismail A Ali2 1Dr. Sumait Hospitals, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, Somalia; 2Department of Surgery, Dr. Sumait Hospitals, Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, SomaliaCorrespondence: Rahmo Mohamed Ali, Email rahmomohameda@simad.edu.soIntroduction: Renal cell carcinoma (RCC) is among the most prevalent kidney malignancies and is characterized by a variety of histological subtypes, with clear cell RCC being the most common subtype. Hypertension may occur as a paraneoplastic manifestation, although the resolution of refractory hypertension following radical nephrectomy remains an uncommon event. To our knowledge, this is the first documented case from a resource-limited setting in which refractory hypertension resolved completely following radical nephrectomy for RCC, underscoring unique diagnostic and therapeutic challenges in such environments.Case Presentation: A 56-year-old male presented with severe uncontrolled hypertension accompanied by persistent headaches and palpitations and was unresponsive to standard anti-hypertensive therapy. Clinical examination revealed a palpable mass in the right flank. Abdominal computed tomography revealed a large, heterogeneous mass (approximately 10 cm) occupying the hepatorenal space, which was initially suggestive of pheochromocytoma. Due to limited diagnostic resources, confirmatory biochemical testing was unavailable. The patient underwent radical nephrectomy and histopathology confirmed clear cell RCC (WHO/ISUP grade 2). The patient’s hypertension resolved completely postoperatively, with subsequent follow-ups demonstrating stable blood pressure and no metastatic disease.Conclusion: This case emphasizes an uncommon presentation of refractory hypertension linked directly to RCC that resolved after radical nephrectomy. This case underscores the importance of considering RCC as a differential diagnosis for refractory hypertension, particularly in resource-limited settings where advanced diagnostics and recent surgical are unavailable.Keywords: renal cell carcinoma, refractory hypertension, radical nephrectomy, paraneoplastic syndrome, case report, Somalia